Emergency Superior Aortic-Mesenteric Venous Bridge - Matteucci, Pablo; Lerena, Ana; Balboa, Oscar; Tiscornia, Eduardo (Cirugía del Uruguay, 1982)
The Aorta mesenteric bypass constitutes an excellent method of intestinal revascularization which can be perfoimed for both chronic and acute occlusions. The authors report on a case and d\scuss this technique